Effectiveness of physiotherapy techniques on depressive symptoms in older adults: a systematic review - Poveda-López, José Lesmes; Jiménez-Sánchez, Carolina; Roy, Juan Francisco; Lafuente-Ureta, Raquel; Aguilera-Gonzalo, Ana (Frontiers in Public Health, 2025)
IntroductionThe older adult population suffers from a high prevalence of depression, representing an increasing burden on healthcare systems. In this context, this systematic review evaluated the effectiveness of physiotherapy for the management of depressive symptoms in this population. The population aged 65 and over is increasing in developed countries such as Spain, currently accounting for 19.09% and projected to reach 25.2% within the next decade. Depression is one of the most prevalent mental health conditions in this group, affecting 5% of community-dwelling individuals and 25% in institutional settings, significantly reducing quality of life and increasing the risk of dementia. While the pharmacological and psychotherapeutic treatments are standard, they present adverse effects and limitations in this population, prompting the exploration of physiotherapy as a non-pharmacological alternative.ObjectiveTo analyze the scientific evidence regarding the effectiveness of combining conventional treatments with physiotherapy techniques for symptomatic improvement in older patients with depression, and to identify the most effective physiotherapy technique, when combined with conventional treatment, for depressive symptoms in older adults.MethodsWe conducted a systematic review following PRISMA guidelines, and we performed searches in PubMed, Web of Science (WOS), Scopus and Cochrane Library databases. Study quality and risk of bias were assessed using the Cochrane Collaboration’s tool.ResultsEight randomized controlled trials, encompassing a total of 1,368 older participants diagnosed with depression or depressive symptoms who received physiotherapy, were included. The findings indicate that physiotherapy techniques, particularly therapeutic exercise, in combination with conventional treatments, may improve depressive symptoms in this population.ConclusionAlthough we observed positive trends in the effectiveness of physiotherapy for depression in older adults, further research is required to validate its clinical efficacy and inform evidence-based treatment guidelines.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251079161.